Changes of plasma fibronectin levels in pregnancy induced hypertension - Paneva-Masin, J; Zafirovska, K; Bogdanovska, S; Lozance, L; Gerasimovska, B (Hrvatska akademija medicinskih znanosti, 2000)
A number of laboratory tests are available for evaluation of hypertension in pregnancy. These tests can be used to either predict and/or prognosticate preeclampsia and other hypertensive disorders of pregnancy. The aim of this study was to evaluate alterations in fibronectin homeostasis in normotensive pregnancy and in hypertensive disorders of pregnancy subclassified into chronic hypertension, preeclampsia superimposed on chronic hypertension, and pregnancy induced hypertension. A prospective, longitudinal study was conducted in 115 pregnant women aged 20-39 years, divided into four groups: normotensive (n = 40), chronic hypertension (n = 18), preeclampsia superimposed on chronic hypertension (n = 20), and pregnancy induced hypertension (n = 37). Plasma concentrations of fibronectin were measured by using single radial immunodiffusion assay (RIA) in the 8th, 18th, 23rd, 28th, 32nd and 36th week of gestation. Plasma fibronectin concentration showed no significant changes in normotensive pregnancy, but was significantly elevated in the third trimester in women destined to become preeclamptic or with preeclampsia in whom it reached a mean (+/- SD) of 0.40 +/- 0.09 g/L in the 36th week of gestation. In the groups with preeclampsia superimposed on chronic hypertension and with pregnancy induced hypertension, there was a significant difference between plasma fibronectin concentrations in 32nd (p < 0.01) and 36th (p < 0.001) week of gestation compared with either other levels in the respective group (in the 8th, 18th, 23rd and 28th week of gestation) or those recorded in other groups in the same period of pregnancy. These results suggested that the measurement of plasma fibronectin might be of diagnostic value in preeclampsia but could not be considered a useful predictor for preeclampsia.